The Inlet Engine Valves Grinding Using Different Types of Cutting Fluids and Grinding Wheels - Silva, Eraldo Jannone Da; Bianchi, Eduardo Carlos [UNESP]; Oliveira, João Fernando Gomes De; Aguiar, Paulo Roberto De [UNESP] (ABM, ABC, ABPol, 2002)
In this paper an experimental research is presented in which different types of cutting fluids (a cutting oil and three different types of soluble oils) and grinding wheels (alumina and vitrified CBN) were tested in the inlet engine valves grinding. As evaluation parameters the workpiece residual stress and the grinding wheel wear were analyzed. The cutting fluid and the grinding wheel types adopted resulted in changes in all the parameters, due to the different lubricant abilities among the fluids and due to the differences in the mechanical and thermal properties among the abrasives tested. For grinding this steel, the CBN wheel is the best choice, mainly due to compressive residual stress results obtained for all cutting fluids tested. The cutting oil is the most adequate cutting fluid to be used, due to its higher lubricity and ability in keeping the wheel sharp for longer periods of time, reducing the overall grinding energy and the thermal damage.
Keywords: grinding wheel; cutting fluid; residual stress